PANDANGAN MASYARAKAT TENTANG PARAMETER KEDEWASAAN PEREMPUAN DALAM PERKAWINAN PERSPEKTIF MASLAHAH AL-MURSALAH: A’YUNINA MAHANANI - A’YUNINA MAHANANI (Fakultas Syariah - IAI Al-Qolam Malang, 2020)
Based on data from the office of religious affairs Wonodadi’s Subdistrict, Regency of Blitar, that in the Kolomayan, Pikatan and Wonodadi villages, population women’s marriage under twenty years old more than other villages. In the third this village, not only many the wealthy but also the poor. This research aims to analyze opinion of societies about criterion women’s maturities as well as who have background santri and non santri in marriage. And then, to analyze attitude of societies about women’s maturities in marriage. The results of this research showed that, opinion of societies about parameter women’s maturities in marriage; the ability in differentiate between benefit and mudharat; the women’s age to marriage are twenty one years old and twenty five years old for men; became a good mother and wife. having attitude each understand, and adequate in financial and emotional. While attitude of societies about women’s maturities in marriage are motivating of education of pesantren, give information about maturity in marrigae to the young; the role of families to build of character of child, and marriage in mature of age.